Zambia : 2003 Article IV Consultation and Ex Post Assessment of Performance Under Fund-Supported Programs-Staff Reports; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines Zambia's 2003 Article IV Consultation and Ex Post Assessment of Performance Under IMF-Supported Programs. Zambia's economic performance has improved significantly in the last four years. After more than two decades of economic decline and inflation averaging more than 50 percent, growth has averaged about 4 percent per year since 2000. The Ex Post Assessment of Performance under IMF-supported programs pointed out that implementation under the Enhanced Structural Adjustment Facility arrangement, approved in 1995, was poor, but generally improved under the Poverty Reduction and Growth Facility arrangement, approved in 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet